Purification of Δ5-3-ketosteroid isomerase from Digitalis lanata. (January 2015) - Meitinger, Nadine; Geiger, Daniel; Augusto, Thierry W.; Maia de Pádua, Rodrigo; Kreis, Wolfgang
Graphical abstract: An enzyme catalyzing the conversion of isoprogesterone (5-pregnene-3, 20-dione) into progesterone (4-pregnene-3, 20-dione) in Digitalis lanata was isolated. The characterization of this enzyme revealed that it resembles the bacterial ketosteroid isomerases. Highlights: Δ 5 -3-Ketosteroid isomerase (3KSI) isomerizes isoprogesterone to progesterone. 3KSI was detected in several plants and isolated from Digitalis lanata leaves. 3KSI was separated from 3β-hydroxysteroid dehydrogenase (3βHSD). The purified 3KSI resembled in its properties the bacterial 3KSI. Abstract: The isomerization of 5-pregnene-3, 20-dione into 4-pregnene-3, 20-dione was investigated to shed further light on cardenolide biosynthesis and to characterize the enzymes involved in cardenolide formation. It was shown that the Δ 5 -3-ketosteroid isomerase of Digitalis lanata, which catalyzes this isomerization, is an individual enzyme and not, as previously thought, associated with Δ 5 -3β-hydroxysteroid dehydrogenase. The enzyme was purified by fractionated ammonium sulfate precipitation, hydrophobic interaction chromatography and gel filtration. The purification protocol resulted in a 68.1-fold enriched specific enzyme activity with a yield of 2.2%. After an additional chromatofocusing step the 3KSI activity appeared as a single protein band at 17 kDa in SDS–PAGE. Plant 3KSI displayed similar properties to microbial 3-ketosteroid isomerases.